2019
DOI: 10.21475/ajcs.19.13.03.p1245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium (Se) application and arbuscular mycorrhizal (AMF) inoculation on soybean (Glycine max) and forage grass (Urochloa decumbens) development in oxisol

Abstract: Fertilizer application can enhance the nutritional value of plants, such effects being influenced by the presence of arbuscular mycorrhizal fungi (AMF). Nutrients × AMF interactions are well-known for variety of elements but very little has been addressed on biofortification of selenium (Se) in plants grown in tropical soils. The purpose of this study was to evaluate the effect of Se application and AMF inoculation on growth and micronutrient contents on soybean plants as forage grass. The experiments were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In previous investigations, the increased efficiency of Se biofortification under AMF inoculation has been documented in several plants, such as Allium species [25], wheat [50], and soybean [51]. Innovatively, the findings from the present research reveal the significant role of AMF in enhancing the I, Se, and Se + I effect on chickpea plants.…”
Section: Quality Indicators and Antioxidants Of Chickpea Seedssupporting
confidence: 72%
See 1 more Smart Citation
“…In previous investigations, the increased efficiency of Se biofortification under AMF inoculation has been documented in several plants, such as Allium species [25], wheat [50], and soybean [51]. Innovatively, the findings from the present research reveal the significant role of AMF in enhancing the I, Se, and Se + I effect on chickpea plants.…”
Section: Quality Indicators and Antioxidants Of Chickpea Seedssupporting
confidence: 72%
“…In previous investigations, the increased efficiency of Se biofortification under AMF inoculation has been documented in several plants, such as Allium species [ 25 ], wheat [ 50 ], and soybean [ 51 ]. Legumes have been reported to positively react to the AMF application in terms on Se accumulation, contrary to lettuce, maize, alfalfa, and forage grass ( Urochloa decumbens ) [ 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The crop absorbed Se from the soil via upward translocation in the root, then distributed Se to different tissues, and ultimately deposited Se in the grain (as reflected by grain Se accumulation). Numerous studies have found that increasing Se concentration in the soil using inorganic Se fertilization has positive impacts on Se accumulation in several crops, including Zea mays, soybean, and wheat [ 21 , 43 , 44 ]. In the current study, we found that fertilizing the soil with selenite could significantly increase the concentration in different parts of soybeans, including roots, leaves and stems, pods, and seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AMFs improved rice production by reducing the total content of As, and improving the nitrogen/carbon (N:C) ratio in rice grains [85,86]. Furthermore, one study reported that selenium (Se) × AMF interactions promoted both soybean and forage grass (Urochloa decumbens) for Se absorption, which improved the quality of the two plants used as animal feed [87]. Rhizoglomus intraradices, one model species of AMFs, help rice, soybean, ginseng (Panax ginseng), and other crops resist drought and cold stresses and promote nutrient absorption [10,88,89].…”
Section: Plant Growth-promoting Fungimentioning
confidence: 99%